CSF omeprazole concentration and albumin quotient following high dose intravenous omeprazole in dogs. (August 2019) - Girod, M.; Allerton, F.; Vangrinsven, E.; Tutunaru, A.C.; de Marchin, J.; Gómez-Fernández-Blanco, C.; Ruiz-Nuño, A.; Wojnicz, A.; Farnir, F.; Gommeren, K.; Peeters, D.
Abstract: Clinical signs of syringomyelia and hydrocephalus occur secondary to cerebrospinal fluid (CSF) accumulation within the central nervous system. Omeprazole is recommended to treat these conditions despite little evidence of its capacity to decrease CSF production in the dog. Studies into new treatments are hampered by difficulties in measuring CSF production. The albumin quotient (QAlb), the ratio between CSF and serum albumin concentrations, may reflect CSF production and any decrease in CSF production should be associated with an increase in QAlb. The primary objective of this study was to determine CSF omeprazole concentration after administration of a high intravenous dose of omeprazole and to evaluate its impact on QAlb in the dog. The second aim was to validate QAlb as a surrogate marker of CSF production. Eighteen dogs were included in this prospective crossover placebo-controlled study. Each dog received omeprazole (10 mg/kg), acetazolamide (50 mg/kg) combined with furosemide (1 mg/kg) and saline. Blood and CSF samples were obtained on day 0 and then every 7 days, one hour after drug administration. Omeprazole concentrations (2.0 ± 0.4 μmol/L) reached in CSF after high dose omeprazole were lower than the concentrations previously described as decreasing CSF production in dogs. There was no significant increase in QAlb following administration of acetazolamide/furosemide, prohibiting validation of QAlb as a surrogate marker for CSF production. Several dogs presented transient mild side effects after injection of acetazolamide/furosemide. High dose omeprazole was well tolerated in all dogs. Highlights: Omeprazole did not reach therapeutic concentration in cerebrospinal fluid after a single intravenous high dose The change in albumin quotient after omeprazole adminstration was not different to the change after placebo. Albumin quotient did not increase after the positive control (acetazolamide plus furosemide) Albumin quotient could not be validated as a surrogate marker for CSF production in dogs. A single intravenous injection of 10 mg/kg omeprazole was well tolerated in healthy dogs.